Effect of different selenium sources on nutrient digestibility, performance and antioxidant status in Mecheri lambs - S S VAJPEYEE; J RAMESH; R KARUNAKARAN; J MURALIDHARAN; V SANKAR; TAPAN KUMAR DAS (Indian Journal of Animal Sciences, 2024)
An experiment was conducted to determine the effect of different selenium sources on nutrient digestibility, performance and antioxidant status in Mecheri lambs. Mecheri lambs (30) were distributed randomly into five equal groups (Control, T1, T2, T3 and T4) with six lambs in each, on the basis of average body weight (14.1±1.1 kg). The animals in T1, T2, T3 and T4 were given sodium selenite (0.30 ppm), selenocysteine (0.30 ppm), nano selenium (0.30 ppm) and nano selenium (0.15 ppm), respectively for 120 days. The result revealed that DM, OM, CP, EE, CF, NDF, ADF and NFE digestibility were significantly higher for lambs in group T2 and T3 than other groups. T3 group showed highest nitrogen intake, retention and balance. There was no difference in daily intake, faecal and urinary excretion and balance of Ca and P. There was no effect on DM intake but T3 and T4 group showed significant difference in body weight gain, average daily gain and feed conversion ratio between the experimental groups. All sources of Se showed no effect on biochemical parameters. However, T3 group showed significantly lower MDA content in blood and significantly higher activity of GSH-Px and SOD compared to other groups. In conclusion, dietary supplementation of Nano-Se at 0.30 ppm can be used more efficiently to improve the nutrient digestibility, growth performance and antioxidant status in Mecheri lambs.